GEOGRAPHY LITERACY OF OBSERVATION INTRODUCTION LANDSCAPE REPRESENTATION PLACE FOR STUDENT EXPERIENCE: (ETHNOMETODHOLOGY PERSPECTIVE) - Fahrudi Ahwan Ikhsan; Fahmi Arif Kurnianto; Elan Artono Nurdin; Bejo Apriyanto (Department of Geography Education, University of Jember, 2018)
This study aims to describe the understanding of geography literacy and student experience with landscape recognition observations using an ethnometodology perspective. The subject of this study was the chairman of each landscape recognition practice group student geography education program from University of Jember. The results of this study that geography literacy has a dimension of relevance to geographic skills in representing contextual phenomena and places from landscape recognition observation activities. The results of both observational studies provide research experience, motivation, critical and scientific thinking skills for students represented in the mapping of the area. Keywords: Geography Literacy, Student Experience, Ethnometodology References Bogdan, R. And Biklen, S.K.(1998). Qualitative Research for Education: An introduction to theories and methods. Boston: Allyn and Bacon, Inc. Boogart II, Thomas A. (2001). The Powwer of Place: From Semiotics to Ethnogeography, Middle States Geograher, 2001, 34: 38-47. Boyle, A., Maguire, S., Martin, A., Milsom, C., Nash, R., Rawlinson, S., Turner, A., Wurthmann, S. & Conchie, S.(2007). Fieldwork is Good: The Student Perception and the Affective Domain, Journaal of Geography in Higher Education, 31(2), 299-317. Chappell, Adrian.(2007). Using Teaching Observations and Reflective Practice to Challenge Conventions and Conceptions of Teaching in Geography, Journal of Geography in Higher Education, 32(2), 257-268. Comber, Barbara.(2017). Literacy Geography and Pedagogy: Imagining Translocal Research Alliances for Educational Justice, Journal Literacy Research: Theory, Method, and Practice, Sagepub, University of South Australia, 66, 53-72. Cotton, Debby R.E., Stokes, Alison, & Cotton, Peter A.(2010).Using Observational Methods to Research the Student Experience, Journal of Geography in Higher Education, 34(3), 463-473. Denzin, Norman K. And Lincoln Yvonna S. (2008). Strategies of Qualitative Inquiry. California: Sage Publications, Inc. Fatchan, Achmad. (2015). Methodology Research Qualitative of Ethnography and Ethnometodology Approaches for Social Sciences. Yogyakarta: Ombak. Guertin, L., Stubbs, C., Millet, C., Lee, T., & Bodek, M.(2012). Enchancing Geographic and Digital Literacy with a Student Generated Course Portfolio in Google Earth, Journal of College Science Teaching, 42(2), 32-37. Hunter, Nancee.(2016). Assesing Sense of Place and Geo-literacy Indicatorc as Learning Outcomes of an International Teacher Professional Development Program, Dissertation, Porland State University. Johnston, B. And Webber, S. (2003). Information Literacy in Higher Education: a review and case study, Studies in Higher Education, 28 (3), 335-352. Levinson, S.C.(2003). Space in Language and Cognition: Explorations in Cognitive Disversity. New York: Cambridge University Press. Lloyd, Annemaree.(2006). Information Literacy Landscapes: an emerging picture, Journal of Documentation, 62 (5), 570-583. Miles, Matthew B, Huberman, A. Michael, and Saldana, Johnny.(2015). Qualitative Data Analysis A Methods Sourcebook. Thousand Oaks, CA: Sage Publications. Minca, Claudio.(2013). The Cultural Geographies of Landscape, Hungarian Geographical Bulletin 62(1), 47-62. National Research Council.(2005). Learning to Think Spatially. GIS as a Support System in the K12 Curriculum. Washington DC: National Research Council and National Academies Press. Ottati, Daniela F.(2015). Geographical Literacy, Attitudes, adn Experiences of Freshman Students: A Qualitative Study at Florida International University, Dissertation. Miami: Florida International University. Patton, M.Q.(2002). Qualitative Research and Evaluation Methods (3rd ed.). Thousand Oasks CA: Sage Publications. Stokes, A. & Boyle, A.P.(2009). The Undergraduate Geoscience Fieldwork Experience: Influencing Factors and Implications for Learning, in: S.J. Whitmeyer, D.W. Mogk & E.J. Pyle (Eds) Field Geology Education-Historical Perspectives and Modern Approach, 461, Geological Society of America, 313-321. Turner, S., & Leydon, J.(2012). Improving Geography Literacy among First Year Undergraduate Students: Testing the Effectivess of Online Quizzes, Journal of Geography, 111(2), 54-66. Â© 2018 Department of Geography Education, University of Jember Copyright Notice This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License